The Influence of Infographic Media on Prospective Brides' Knowledge about Reproductive Health - Nurul Ananda; Basri Aramico; Fahmi Ichwansyah; Said Usman; Asnawi Abdullah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Reproductive health is an important aspect that every prospective bride and groom must understand to prepare for a healthy and quality family life. However, the low level of knowledge of prospective brides and grooms is a challenge in efforts to prevent reproductive health risks. This study aims to determine the effect of infographic media on prospective brides and grooms' knowledge of reproductive health. The research design used a quasi-experimental approach with a one-group pretest-posttest. A total of 88 respondents were selected purposively from four Religious Affairs Offices in Banda Aceh City. The instrument in the form of a questionnaire tested for validity and reliability was given before and after the intervention using infographic media. The analysis showed a significant increase in knowledge scores from an average of 9.02 in the pretest to 18.86 in the posttest (p = 0.000). However, multivariate analysis showed that the variables of age, gender, education, occupation, and income did not significantly affect changes in knowledge (p > 0.05). Infographic media has been proven to effectively convey information visually and increase the understanding of prospective brides and grooms regarding basic concepts of reproductive health more easily and attractively.